A novel S-type CsxWO3/BiOI heterojunction photocatalyst constructed in graphene aerogel with high degradation efficiency for enrofloxacin: Degradation mechanism and DFT calculation. Issue 2 (April 2023) - Li, Tianci; Liu, Jingxiao; Shi, Fei; Zhang, Haoyuan; Zhang, Haojie; Ma, Chuangchuang; Wasim, Muhammad
Abstract: The construction of semiconductor heterojunction photocatalyst is an effective way to improve the photocatalytic performance. In this study, a novel S-type heterojunction Csx WO3 /BiOI photocatalyst, with both photothermal effect and good photocatalytic activity, was constructed in graphene aerogel. The as-prepared composite aerogel showed high adsorption/photocatalytic activity and cycling stability for removal of enrofloxacin. Especially, the aerogel sample 1.0CIGA with Csx WO3 :BiOI molar ratio 1.0 showed a high removal efficiency of enrofloxacin with attaining to nearly 100% within 60 min. Moreover, the photothermal conversion effect of Csx WO3 can further promote the photocatalytic degradation reaction efficiency. The degradation intermediate products and possible degradation pathways of enrofloxacin were analyzed and explored. In addition, the energy band structure and charge transfer mechanism of Csx WO3 /BiOI heterojunction were studied by density functional theory (DFT) and other test methods. This work is of great significance for developing efficient photocatalytic materials and the as-prepared Csx WO3 /BiOI@graphene composite aerogel with high adsorption/photothermal catalysis will have promising applications in the field of environmental purification. Graphical Abstract: ga1 Highlight: A novel s-type Csx WO3 /BiOI heterojunction was constructed in graphene aerogel. The composite aerogels showed excellent removal efficiency for enrofloxacin. The degradation pathway of enrofloxacin by Csx WO3 /BiOI@graphene aerogel was analyzed.